Proceso contable del sindicato de obreros de la salud del Hospital Básico de Baba, provincia de Los Ríos. - León Ramírez, Angélica María (2022)
The present investigation entitled "Accounting Processes of the Union of Health Workers of the Basic Hospital of Baba, Province of Los Ríos", aims to identify the internal control of the accounting processes of the Union of Workers of the Basic Hospital of Baba in the city of Baba , this is carried out through a qualitative methodology, with observation and interview tools, for the development and search of information, the research line of the Technical University of Babahoyo "Financial, Tax Management and Social Commitment" is taken into account. ” and the sub-line “Audit and Control” considered as one of the bases of the race to delimit the influence of an internal control within the accounting processes of the organization. The results or conclusions that are given at the end of the investigation are that the organization does not comply with a correct accounting process, which leads to the strategies and decisions used being incorrect, a demonstration is made of what the correct entry of information would be like. accountant for a random income movement of the monthly fees of the partners.